The use of force in international law and its implications for international relations - Bouloussakh, Imane; Mallem, Youcef (Journal of Human Sciences, 2020)
The use of force in international law and armed force in general is one of the methods that the state used to protect its interests and impose its point of view, and international precedents clarify the resulting loss of lives and money without leading to the resolution of disputes, but rather its use carries within it a great danger for the states used Against it is strength, as the international community intends on this occasion to mobilize the largest amount of military force to implement the decisions issued by the United Nations, and this marks the beginning of a new history of humanity. One of its foundations is the rule of the law of the most powerful, excluding international law and imposing hegemony on the international community